Проектирование информационной системы управления вертикально-интегрированными агрохолдингами - Шматко, Александр Витальевич; Фонта, Н. Г.; Манева, Р. И. (НТУ "ХПИ", 2015)
В работе рассматривается подход к проектированию и разработке информационных систем для управления и оптимизации организационной структуры вертикально-интегрированных агрохолдингов. Выполнен обзор проблемы построения и улучшения организационной структуры вертикально-интегрированного агрохолдинга. Предложен метод построения дискретной модели структуры управления агрохолдингом, которая обеспечивает минимизацию издержек, связанных с привлечением претендентов к работе.

The paper deals with an approach to the design and development of information systems for the management and optimization of the organizational structure of vertically integrated agricultural holdings. A review of the problems of building and improving the organizational structure of vertically integrated agricultural holding is made. A method of constructing a discrete model management structure agricultural holding, which minimizes the costs associated with attracting applicants to work, is proposed.
Design of information management system of vertically integrated agricultural holdings
Keywords: информационные обеспечение; управление организационной структурой; математическое обеспечение; программное обеспечение; стратегическое управление агрохолдингом; information management; system software; management organizational structure; vertically integrated agricultural holding; mathematical information system; software information system; strategic management agricultural holding